2006
DOI: 10.1007/s00467-006-0145-z
|View full text |Cite
|
Sign up to set email alerts
|

GFR is better estimated by considering both serum cystatin C and creatinine levels

Abstract: Serum cystatin C (cysC) is a potential marker of the glomerular filtration rate (GFR) that has generated conflicting reports in children. A prospective study was conducted to assess the benefit of considering cysC together with serum creatinine (SCr) and demographic and morphologic characteristics to better estimate the 51Cr-ethylenediaminetetraacetate (EDTA) clearance (CL), i.e., the GFR. Plasma 51Cr-EDTA data from 100 children or young adults (range: 1.4-22.8 years old) were analyzed according to the populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
77
0
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(90 citation statements)
references
References 23 publications
(22 reference statements)
4
77
0
8
Order By: Relevance
“…In children, age and body mass do not significantly affect cystatin C eGFR (13). The known confounders affecting cystatin C levels such as corticosteroids and thyroid status cannot explain the variability in the performance of different cystatin C equations either (3,8,11). Previous studies have demonstrated that the variance between cystatin C eGFR and measured GFR increases in the high GFR range when compared with that in the low GFR range (3,13).…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…In children, age and body mass do not significantly affect cystatin C eGFR (13). The known confounders affecting cystatin C levels such as corticosteroids and thyroid status cannot explain the variability in the performance of different cystatin C equations either (3,8,11). Previous studies have demonstrated that the variance between cystatin C eGFR and measured GFR increases in the high GFR range when compared with that in the low GFR range (3,13).…”
Section: Introductionmentioning
confidence: 95%
“…Cystatin C eGFR was calculated using the previously published Bö kenkamp (2), Bouvet (8), CKiD (11), Filler (6), Grubb (4), and Zappitelli (3) equations. The published equations are shown in Table 1.…”
Section: Calculation Of the Estimated Gfrmentioning
confidence: 99%
See 2 more Smart Citations
“…Estimated GFR values were calculated using four Scr-based equations (Schwartz [20], Flanders Metadata [19], simple height-independent [21], Q(height) [22]), three CysC-based equations (Larsson [23], Filler [24], Zappitelli [25]) and two Scr/CysC-based equations (Zappitelli [25], Bouvet [26]). Only formulas based on enzymatic Scr and/or nephelometry were included.…”
Section: Estimated Gfr (Egfr)mentioning
confidence: 99%